Ultrasensitive protein-level detection for respiratory infectious viruses - Kobayashi, Yuki; Kyosei, Yuta; Ogawa, Ryutaro; Okita, Kyo; Yoshimura, Teruki; Ito, Etsuro (Frontiers in Immunology, 2024)
Influenza virus, adenovirus, and respiratory syncytial virus cause major respiratory infections. These infections have similar initial symptoms making it difficult to differentiate them based on symptoms alone. PCR is currently used as the standard diagnostic test for these infections, however, it has its limitations such as non-specific and false-negative amplifications, high cost, and the inability to distinguish between a live or dead virus. Therefore, there is a need for alternative diagnostic methods that focus on protein. Here, we introduce TN-cyclon™, which is an enzyme-linked immunosorbent assay combined with thio-nicotinamide adenine dinucleotide cycling to amplify signals, rather than the protein itself. Using this method, we were able to detect extremely low levels of viruses such as influenza A, influenza B, adenovirus, and RS virus, with LODs of 2.96 × 10-18 moles/assay, 2.98 × 10-18 moles/assay, 2.36 × 10-18 moles/assay, and 3.55 × 10-18 moles/assay, respectively. Furthermore, we successfully detected viruses diluted with extract buffer, with a significant difference to the blank at concentrations of 3 pfu/mL for influenza A, 1000 pfu/mL for influenza B, 43.8 pfu/mL for adenovirus, and 125 pfu/mL for RS virus. This shows that our low-cost and easy-to-use technique has sufficient sensitivity in diagnosing respiratory infections.